TEMPORARY INTRALUMINAL SHUNTING UNDER CONDITIONS OF A PARALLEL CARDIOPULMONARY BYPASS - R. V. Sidorov; A. A. Petyaev; A. M. Petyaev; D. Y. Pospelov; N. S. Doltmurzieva; V. N. Shchetko (Медицинский вестник Юга России, 2016)
Purpose: to study the effect of application of intraluminal coronary bypass grafts on the intra- and early postoperative periods in patients with coronary artery disease, who underwent a direct myocardial revascularization under conditions of a parallel cardiopulmonary bypass.Material and methods: the study included patients with multiple lesions of coronary arteries with an ejection fraction 51,2% ± 5,3. The patients were randomised into 2 groups: in the first group (n = 41) the cardiopulmonary bypass operation was accompanied by using intraluminal coronary grafts; in the second group (n = 52) - without this procedure. The superior effectiveness of the graft procedure was assessed by lesser changes in ST-segment of ECG during and after the operation, fluctuations in cardiac index, the value of the plasma fraction of cardiac creatine phosphokinase, and a number of complications during the intra-and postoperative periods.Summary: based on these data it was concluded the advantage of application of intraluminal coronary bypass grafts with direct revascularization in parallel artificial circulation.